IMPLEMENTATION AND EDUCATION OF THE COMBINATION THERAPY OF SWEDISH MASSAGE AND ACUPRESSURE FOR ELDERLY WITH LOW BACK PAIN: CASE STUDY - Fadillah Puspa Nadinnisa; Wastu Adi Mulyono; Galih Noor Alivian (International Journal of Biomedical Nursing Review, 2025)
Introduction: Low back pain (LBP) is a common complaint experienced by the elderly. LBP can occur due to a history of static work positions. One complementary therapy to address chronic pain is a combination of Swedish massage and acupressure. Massage therapy is well-known as a pain relief method in Banteran Village. With education on Swedish massage and acupressure for families with LBP clients, pain management can be carried out properly and independently. Purpose: The objective of this case study is to investigate the effect of a combination therapy of Swedish massage and acupressure on low back pain in the case of Mrs. R. Methods: This study used a single-subject study method, which focuses on observing and analyzing the changes felt by individuals after receiving a combination of Swedish massage and acupressure therapy. The intervention was performed 8 times, with a two-day interval between sessions. The researcher asked the client to rate their pain level on a pain scale and measured blood pressure before and after therapy. Discussion: The results of the combined Swedish massage and acupressure therapy on the elderly patient, Mrs. R, showed a reduction in pain scale after 8 sessions with a frequency of every other day. The pain level decreased from moderate to mild, and blood pressure was reduced by 23-11 mmHg systolic and 15-8 mmHg diastolic. The pain reduction was due to the release of endorphins, which help relax the body. However, the pain returned afterward due to excessive physical activity. This therapy can be performed independently by Mrs. R's family. Conclusion: There was a reduction in the pain scale of low back pain (LBP) experienced by the client before and after the combination therapy of Swedish massage and acupressure. The intervention can also be performed independently by the family. Keywords: acupressure, low back pain, Swedish massage